A Study on Addressing Unemployment: Strategies and Policies for Enhancing Job Creation - Radha, P; Nirubarani, J.; Mekala, S. (NPRC Journal of Multidisciplinary Research, 2024)
Unemployment remains a critical challenge impacting economies globally, affecting individual livelihoods and economic stability. This study explores various strategies and policies designed to mitigate unemployment and foster job creation. The research reviews historical and contemporary approaches, evaluating their effectiveness and adaptability to current economic conditions. The study begins with an examination of the root causes of unemployment, including structural, cyclical, and frictional factors. By analyzing these underlying issues, the research identifies the need for targeted interventions. Key strategies discussed include investment in education and vocational training, which aims to align workforce skills with market demands, and the promotion of entrepreneurship and small business development as means to stimulate job creation. Additionally, the research delves into policy frameworks such as unemployment benefits and job search assistance programs, which can provide temporary relief and support to unemployed individuals while they seek new opportunities. The study also assesses the impact of economic policies, such as fiscal stimulus and monetary policy, on job creation and economic growth. The research employs a comparative analysis of various countries and their approaches to unemployment, drawing lessons from successful case studies and highlighting areas where policy improvements are needed. It also considers the role of technology and innovation in transforming job markets, including the potential of digital platforms and remote work to create new employment opportunities. Furthermore, the study explores the importance of inclusive policies that address disparities in employment based on gender, age, and socio-economic background. Ensuring equal access to job opportunities and reducing barriers to employment are crucial for achieving sustainable economic growth. The findings underscore the importance of a multifaceted approach that combines immediate relief measures with long-term strategies to enhance job creation. The study concludes with recommendations for policymakers to design and implement integrated policies that address the diverse aspects of unemployment and leverage opportunities for growth in a rapidly evolving economic landscape.